Comparison Analysis of Indomaret Brand Equity With Alfamart (Wiliam Iskandar) - Missy Bremila; Matondang, Vinsensius; Hendra (MAMEN: Jurnal Manajemen, 2022)
Indomaret and Alfamart are retail businesses that continue to grow in the city of Medan. With retail growth that continues to grow, brand equity will be an important grower because a brand can be declared good if it has strong brand equity.This study aims to determine the difference in brand equity between Indomaret and Alfamart where the study uses the theory of Building strong brands. The research was conducted by comparing the size of the percentage of answers on the questionnaire. For testing the instrument using validity, reliability and normality tests. Meanwhile,The analysis used by the author is percentage analysis and analysis of the Independent Sample Test. Analysis of the Independent Sample Test is a statistical test used to compare the observation data with the expected data to test the hypothesis. The results show that there are differences in Brand Equity between Indomaret and Alfamart in the minds of consumers based on the dimensions of Brand Awareness, Brand Association, Quality Perception and Brand Loyalty. Of the four dimensions of Brand Equity, there are 2 (two) dimensions which state that there are differences between Indomaret and Alfamart. And there are 2 (two) dimensions which state that there is no difference between Indomaret and Alfamart. From these four dimensions, Indomaret is superior to Alfamart.